ASSESSMENT OF QUALITY OF LIFE IN LUNG CANCER PATIENTS UNDERGOING CHEMOTHERAPY AT A TERTIARY CARE HOSPITAL - AYUSH GIRI; VAISHALI PANDA; ANKIT AGARWAL; MAHENDRA SINGH RATHORE; AVI SHAH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: To assess the quality of life (QOL) in lung cancer patients during initial chemotherapy cycles. Methods: A prospective observational study was conducted at Geetanjali Medical College and Hospital, Udaipur, on patients with lung cancer being treated with chemotherapy from July 2023 to June 2024. QOL of patients was assessed using the functional assessment of cancer therapy – (FACT-G Version 4) with approval. Results: One hundred and eighteen patients were included in the study using the purposive sampling method. A total of 127 subjects were screened during the recruitment process out of which nine participants refused to give their consent. Out of the total participants, 83.9% were males and 16.1% were females with a mean age of 59.7 years. 93.2% of patients were diagnosed with non-small cell lung cancer and the remaining 6.8% were small cell lung cancer. The most commonly prescribed drug was carboplatin (72.88%) followed by paclitaxel (55.93%). There was no statistical difference found in physical, social, emotional, and functional well-being before starting of the first and ending of the third chemotherapy cycle. Conclusion: Our study concludes that there is no significant short-term effect on the physical, functional, social, and emotional well-being of the patients on chemotherapy for lung cancer.